New stains for anterior capsule surgery. Issue 2 (February 2019) - Wilińska, Joanna; Mocanu, Bianca; Awad, Doaa; Gousia, Dimitra; Hillner, Charlie; Brannath, Werner; Mohr, Andreas; Gabel, Detlef
Abstract : Purpose : To investigate whether new dyes and dye combinations can give equivalent or better staining in anterior capsule surgery than existing dyes with a low degree of toxicity on relevant cells. Setting : University laboratory of Jacobs University Bremen, Germany. Design : Laboratory experimental study. Methods : Pig eyes were collected post mortem. Cataract was induced by microwave irradiation. Access to the lens capsule was through open‐sky surgery. Staining was performed and results were documented by photography. The toxicity of the dyes was evaluated in 3 different cell lines immediately after exposure and with a delay of 24 hours, with exposure in the dark or subsequent strong illumination. Results : A new cyanine dye, BIP (2‐[5‐[3, 3‐dimethyl‐1‐(4‐sulfobutyl)‐1, 3‐dihydro‐indol‐2‐ylidene]‐penta‐1, 3‐dienyl]‐3, 3‐dimethyl‐1‐(4‐sulfobutyl)‐3H‐indolium sodium), was found to lead to green staining, with reduced toxicity on corneal endothelial cells. Staining could be further enhanced by combining it with trypan blue. Methylene blue was very toxic, whereas its combination with trypan blue was much less toxic. Conclusions : With BIP alone or in combination with trypan blue, safe staining of the capsule can be achieved, resulting in a green color.